Hubungan Pola Asuh Ibu Bekerja terhadap Kemandirian Anak Usia 5-6 Tahun di TK Al-Hidayah Maibit - Roudlotun Nikmah; Ida Fauziatun Nisa' (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2021)
This study aims to reveal the relationship between parenting patterns of working mothers and the independence of children aged 5-6 years in Al-Hidayah Maibit Kindergarten, with the formulation of the problem: 1) working mothers parenting, 2) independence of children aged 5-6 years in Al-Hidayah Kindergarten. Maibit, and 3) the relationship between working mothers' parenting patterns on the independence of children aged 5-6 years. This research belongs to the type of quantitative research with statistical methodology. The data used are primary and secondary data obtained through the process of extracting data using documentation and questionnaire methods. The data were analyzed by using Product Moment correlation analysis technique. From the results of data analysis, the following conclusions were obtained: 1) The parenting pattern of working mothers for their children in Al-Hidayah Maibit Kindergarten strongly trains children's independence, as evidenced by the high percentage of filling out questionnaires on statements about parenting that trains children's independence 2) Independence of children aged 5- 6 years in Al-Hidayah Kindergarten is very good, as evidenced by the results of the questionnaire which shows that on average the children are able to show their independence and 3) There is a relationship between the parenting pattern of working mothers and the independence of children aged 5-6 years in Al-Hidayah Maibit Kindergarten. This is evidenced by the results of the calculation of product moment 0.520 which is greater than (r) table both in the 1% and 5% significance level.